Unfriendly fire : a mother's memoir - Mullen, Peg, 1917-2009 (Singular lives., 1995)
In 1968 Michael Mullen, a graduate student in biochemistry, was drafted. In 1969 he was sent to Vietnam as a foot soldier in Colonel Norman Schwarzkopf's Charlie Company; and in 1970 he was killed by the same "friendly fire" that destroyed thousands of other lives during the Vietnam War. Back home on the family farm in Iowa, his parents made his death a crusade to awaken all parents to the insanity of war. C.D.B. Bryan's Friendly Fire and the TV movie of the same name documented these dramatic years, and Peg Mullen became a national symbol of grassroots activism.